The Relationship Between BRCA1 Expression and Grade in Breast Cancer Patients in NTB - Mikailla, Romy Healthy; Padauleng, Novrita; Lestari, Rizka Vidya; Prihatina, Lale Maulin; Priyanto, Bambang; Kumaladewi, Baiq Ratna (Jurnal Biologi Tropis, 2025)
Breast cancer is the malignancy with the highest incidence among women in West Nusa Tenggara (NTB). The Breast Cancer 1 (BRCA1) gene is a tumor suppressor gene that plays a crucial role in DNA repair and genome stability. A decrease in BRCA1 expression is theoretically associated with more aggressive tumor characteristics, such as a low degree of differentiation (high grade). However, data regarding the relationship between BRCA1 protein expression and the degree of cell differentiation in the patient population in NTB remains limited. This study employed a cross-sectional design with an observational analytic approach on 50 paraffin block samples from Invasive Breast Carcinoma patients at the NTB Provincial General Hospital from 2022-2023. BRCA1 protein expression was assessed using immunohistochemistry with a positive cut-off defined as staining in >20% of tumor cell nuclei. Data on the degree of differentiation (Grade 1, 2, and 3) were obtained from medical records. The relationship between the two variables was analyzed using the Lambda, Pearson’s R, and Spearman Correlation tests with a significance level of p < 0.05. The majority of samples (84%) were grade 3 tumors. The distribution of BRCA1 expression in the total sample was balanced, with 25 cases (50%) showing positive expression and 25 cases (50%) showing negative expression. In the grade 3 subgroup, this distribution remained balanced. Statistical analysis consistently showed no significant relationship between BRCA1 expression and the degree of cell differentiation (p > 0.05).